Peningkatan Keterampilan Proses Sains Melalui Kegiatan Laboratorium Disertai Strategi Catatan Terbimbing (Guided Note Taking) Pada Siswa Kelas VIII E SMP Negeri 7 Surakarta Tahun Pelajaran 2010/2011 - Anggita Widya Nugroho; Meti Indrowati; Bowo Sugiharto (Universitas Sebelas Maret, 2013)
The purposes of this research is to improve the science process skills through applying laboratory activity with guided note taking to the students of VIII E class at SMP Negeri 7 Surakarta, academic year 2010/2011. This research refers to The Classroom Action Research which is conducted in 2 cycles that consist of planning, action, observing, and reflecting. The subject of this research is 36 students of VIII E class at SMP Negeri 7 Surakarta, academic year 2010/2011. The sources of the data consist of information from teachers and students, places and events that happened during the process of teaching and learning, and also some documents/files. The data of this research is collected by using observation sheet, questionnaire, interview, and documentations. The data is analyzed in qualitative descriptive method. The validity of data is tested through method and observer triangulation. The result of this research shows that has done in two cyrcles can be concluded that the application of laboratory activity with guided note taking can improve the science process skills in observe, clasificate, predict, measure, conclude, and communicate skills of the student of VIII E class at SMP Negeri 7 Surakarta, academic year 2010/2011. Key Words: Science Process Skills, Laboratory Activity, Guided Note Taking